The Use of Artificial Intelligence-Based Generative Learning Media to Improve Arabic Language Learning Strategies - Ibnu Fazar; Khasan Aedi; Durtam Durtam (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
The rapid development of generative Artificial Intelligence (AI) has created new opportunities for interactive and adaptive learning media in Arabic language education. Tools such as ChatGPT and Chatbot AI enable dialogic interaction, immediate feedback, and personalized learning experiences that support students in practicing language skills and accessing learning resources. However, existing studies on generative AI in Arabic language learning often focus primarily on learning outcomes, while the role of these technologies in supporting students’ learning strategies has received limited systematic attention. This study aims to systematically examine the forms and pedagogical characteristics of generative AI-based learning media, analyze their association with the development of students’ learning strategies, and identify pedagogical and contextual challenges in implementation. This research employs a qualitative Systematic Literature Review (SLR) method guided by the PRISMA framework, with interpretation supported by the Technology Acceptance Model (TAM). Fifteen studies published between 2021 and 2025 were selected from Google Scholar and Crossref databases based on predefined inclusion and exclusion criteria. The findings indicate that ChatGPT and Chatbot AI are widely used to support speaking, writing, translation practice, adaptive feedback, and independent learning in Arabic language learning. These technologies function as external scaffolds that facilitate learning planning, resource management, and learning process monitoring. The study concludes that generative AI has significant potential to support strategic learning development in Arabic language education, although its implementation still faces challenges related to linguistic accuracy, ethical considerations, and disparities in digital literacy and technological infrastructure.